Pengembangan Media Pembelajaran Game Edukasi Tajwid Berbasis Android - Khozainuz Zuhri; Ahmad Ikhwan; Hamdan Sukri; Rusman Ependi (Universitas Mitra Indonesia, 2022)
Technology brings people to see beyond the outside world, open their minds to think, and build creativity to create new things. One technology that is currently developing very rapidly is technology in the form of smartphones, especially those based on Android. Android games are one of the entertainment media that are the people's choice to eliminate boredom or just to fill spare time. In addition to being a medium of entertainment, games can also be a medium of learning to improve one's brain development. Learning media such as interactive Tajweed science using educational game media are still rare, even educational games with the theme of learning about Tajweed Science are not yet available. Android-Based Tajweed Educational Game Design which is expected to provide education, convenience and entertainment that are more interesting, efficient, effective, and efficient.